A resurgence of eugenics? The role of race in egg donation - Moyo, Rufaro (Department of Sociology, 2020)
Despite the Human Genome Project in 2000 discovering that there is no hereditary distinction between races, the naturalized bio-centric conception of race continues to pervade our society (Roberts, 2011). One such area where this happens is during the egg donation process. Egg donation is a part of the growing industry of Assisted Reproductive Technologies (ARTs), which clinics employ in the treatment of infertility. Donor agents and clinics often classify their donors using racial categories. This research project sought to discover what role race played in the egg donation process, using racial matching and neo-eugenics as its theoretical frameworks. Ten semi-structured open ended interviews were conducted with nine participants, all of whom work in the field of fertility. The study discovered that the role race plays in the egg donation process is central. Both recipients and donor agents employ racial categories in order to find an egg donor that racially matches the patient, which is the phenomenon of racial-matching. This phenomenon of race-matching is a process of neo-eugenics. Whilst many think of ‘better birth’ at the mention of the term eugenics, this study makes the argument that racial matching mimics eugenic practices of maintaining the myth of racial purity. Donor agents speak of an ‘obviousness’ of the use of racial categories, naturalizing race as biological and seemingly legitimizing hegemonic notions of the family. Yet despite the prevalent use of race, donor agents display discomfort in discussing race and employ emotional narratives that speak to the fairy tale of a supposedly racially homogeneous and heterosexual family being made as a means of deflecting possible problematic views of egg donation. The study acknowledges the socio-political issues that often underpin ARTs, which is carefully concealed by narratives of family creation and the search for wellness. The study concludes by reiterating these arguments and making mention of the need for these power dynamics surrounding race to be dismantled to achieve social justice for all.